2021
DOI: 10.4314/ovj.v10i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided serratus plane block as an effective adjunct to systemic analgesia in four dogs undergoing thoracotomy

Abstract: Background: Ultrasound-guided serratus plane block (UGSPB) is a loco-regional anesthesia technique designed to desensitize the thoracic wall. It is a compartmental block, where local anesthetic is delivered to the fascial, intermuscular plane. Since its original description in humans, two cadaveric veterinary studies, redefining the technique, have been performed. Taking into account the successful use of the UGSPB in human medicine, we employed the veterinary description to perform this block in four dogs und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In veterinary medicine, neuraxial techniques and peripheral anaesthetic blocks, as thoracic paravertebral block, erector spinae plane block, serratus plane block, intercostal blocks or pleural irrigation with local anaesthetics, have been used to provide chest wall analgesia [4][5][6][7][8][9]. No studies have been reported suggesting the efficacy of the TTP block to provide analgesia to the ventral aspect of the chest wall in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, neuraxial techniques and peripheral anaesthetic blocks, as thoracic paravertebral block, erector spinae plane block, serratus plane block, intercostal blocks or pleural irrigation with local anaesthetics, have been used to provide chest wall analgesia [4][5][6][7][8][9]. No studies have been reported suggesting the efficacy of the TTP block to provide analgesia to the ventral aspect of the chest wall in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Two different case series have investigated the analgesic efficacy of serratus plane block 18 and erector spinae plane block 19 in dogs submitted to lateral thoracotomy. More recently, another case series reported the use of erector spinae plane block in combination with a constant‐rate infusion of dexmedetomidine in dogs submitted to sternotomy 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that both of these techniques have already been described in cadaveric studies in dogs, 16,17 the clinical evidence of their use for thoracotomies is still scarce in veterinary anaesthesia. UG‐SPB prevented nociception and reduced the intraoperative opioid requirements in four dogs undergoing lateral thoracotomy 18 . Similarly, UG‐ESPB as part of MA provided good intraoperative analgesia in six dogs undergoing lateral thoracotomy 19 .…”
Section: Introductionmentioning
confidence: 90%
“…UG-SPB prevented nociception and reduced the intraoperative opioid requirements in four dogs undergoing lateral thoracotomy. 18 Similarly, UG-ESPB as part of MA provided good intraoperative analgesia in six dogs undergoing lateral thoracotomy. 19 To the authors' knowledge, neither of these LA techniques has been described yet in cats undergoing thoracic surgery.…”
Section: Introductionmentioning
confidence: 94%